2015
DOI: 10.1007/s12039-014-0749-y
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependent non-ideality in aqueous binary mixtures as a signature of avoided spinodal decomposition

Abstract: We explore the potential energy landscape of structure breaking binary mixtures (SBBM) where two constituents dislike each other, yet remain macroscopically homogeneous at intermediate to high temperatures. Interestingly, we find that the origin of strong composition dependent non-ideal behaviour lies in its phase separated inherent structure. The inherent structure (IS) of SBBM exhibits bi-continuous phase as is usually formed during spinodal decomposition. We draw analogy of this correlation between non-idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Požar et al studied the spatiotemporal heterogeneity of water/methanol mixtures at a wide range of temperatures. The amphiphilicity of methanol molecules reinforces the microheterogeneity of the structure even at room temperature as seen in aqueous solutions of other amphiphiles. , These microsegregated domains are longer lived at a lower temperature. The structural heterogeneity has a strong impact on the dynamic heterogeneity of the medium, which actually indicates the co-existence of mobile domains of different mobilities in the same system.…”
Section: Resultsmentioning
confidence: 99%
“…Požar et al studied the spatiotemporal heterogeneity of water/methanol mixtures at a wide range of temperatures. The amphiphilicity of methanol molecules reinforces the microheterogeneity of the structure even at room temperature as seen in aqueous solutions of other amphiphiles. , These microsegregated domains are longer lived at a lower temperature. The structural heterogeneity has a strong impact on the dynamic heterogeneity of the medium, which actually indicates the co-existence of mobile domains of different mobilities in the same system.…”
Section: Resultsmentioning
confidence: 99%
“…Their work reveals that not all water and alcohol models show molecular aggregation. Banerjee and Bagchi 32,33 have shown that the existence of TBA clusters in the low TBA concentration is because of the so-called Janus effect. They have found that the lifetime of these clusters spans up to a few tens of picosecond for water-TBA mixture.…”
Section: Introductionmentioning
confidence: 99%
“…These quantities have a flat asymptote which corresponds to the value of the KBI according to Eqs. (4) and (9), which can be evaluated graphically. In the case of domain formation, the RKBI reach the asymptote through domain oscillations, which range can exceed the simulation box size.…”
Section: B Computational Detailsmentioning
confidence: 99%
“…7,8 However, the exact status of this microheterogeneity (MH), as well as the consequences of its existence upon thermophysical properties of such systems, is not well understood. 8,9 One point that we have investigated in our previous works 8 is how to distinguish the microheterogeneity (MH) from concentration fluctuations (CF), the latter which are accessible through the Kirkwood-Buff integrals [10][11][12] (KBI). The difference between CF and MH relates, respectively, to the k = 0 part of the structure factors (associated to the KBI) and the k 0 part corresponding to the pre-peak in partial structure factors associated with hydrogen bonding atoms.…”
Section: Introductionmentioning
confidence: 99%